The origins of gender differences in competitiveness and earnings expectations: Causal evidence from a mentoring intervention - Teodora Boneva; Thomas Buser; Armin Falk; Fabian Kosse (Tinbergen Institute, 2021)
We present evidence on the role of the social environment for the development of gender differences in competitiveness and earnings expectations. First, we document that the gender gap in competitiveness and earnings expectations is more pronounced among adolescents with low socioeconomic status (SES). We further document that there is a positive association between the competitiveness of mothers and their daughters, but not between the competitiveness of mothers and their sons. Second, we show that a randomized mentoring intervention that exposes low-SES children to predominantly female role models causally affects girls' willingness to compete and narrows both the gender gap in competitiveness as well as the gender gap in earnings expectations. Together, the results highlight the importance of the social environment in shaping willingness to compete and earnings expectations at a young age.
Keywords: 330; competitiveness; gender; socioeconomic status; inequality; earnings expectations